2021
DOI: 10.1007/s11845-021-02858-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of blood CDC42 level with Th1 cells, Th17 cells, inflammation markers, disease risk/activity, and treatment efficacy of rheumatoid arthritis

Abstract: Background Cell division control protein 42 (CDC42) is reported to be involved in multiple inflammation processes by regulating T cell differentiation, maintaining immune cell homeostasis, and altering their function, while no relevant studies explored its clinical role in patients with rheumatoid arthritis (RA). Therefore, this study aimed to explore the correlation of CDC42 with Th1 and Th17 cells and its association with disease risk, activity, and treatment outcomes of RA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…16,17 Furthermore, CDC42 is inversely correlated with disease activity score in 28 joints (DAS28), Bath ankylosing spondylitis disease activity index (BASDAI), and pediatric CD activity index (PCDAI) in RA patients, AS patients, and pediatric CD patients, respectively. [16][17][18] In the current study, CDC42 was negatively related to CRP, TNFα, IL-1β, IL-17A, and Mayo score in active UC patients, which could be explained as that: (a) CDC42 mediated multiple signaling pathways to suppress the inflammatory markers and cytokines in UC patients. 24,25 (b) CDC42 was related to less intestinal inflammation as mentioned earlier, which prevented the intestinal mucosal barrier from irritation and disruption, therefore leading to lower disease activity of UC patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16,17 Furthermore, CDC42 is inversely correlated with disease activity score in 28 joints (DAS28), Bath ankylosing spondylitis disease activity index (BASDAI), and pediatric CD activity index (PCDAI) in RA patients, AS patients, and pediatric CD patients, respectively. [16][17][18] In the current study, CDC42 was negatively related to CRP, TNFα, IL-1β, IL-17A, and Mayo score in active UC patients, which could be explained as that: (a) CDC42 mediated multiple signaling pathways to suppress the inflammatory markers and cytokines in UC patients. 24,25 (b) CDC42 was related to less intestinal inflammation as mentioned earlier, which prevented the intestinal mucosal barrier from irritation and disruption, therefore leading to lower disease activity of UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CDC42 is reduced in AS patients, RA patients, and pediatric CD patients compared with controls. [16][17][18] Also, CDC42 is related to a lower risk of active CD in children, 18 while the clinical value of CDC42 in UC patients remains exclusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th1 and Th17 cell subsets contribute to inflammation in RA. Many studies have shown that the inhibition of Th1 and Th17 cell subsets can alleviate RA (77)(78)(79). Th2 cell subsets can inhibit Th1 and Th17 cell differentiation and function by secreting IL-4 as a mechanism to antagonize inflammation (80).…”
Section: The Effect Of Dna Methylation On the Differentiation Of Cd4+...mentioning
confidence: 99%